Pengaruh Sistem Kompensasi, Fleksibilitas Kerja, dan Stres Kerja terhadap Kinerja Mitra Driver Grab Kota Semarang - Muhamad Didik Setiawan; Batara Daniel Bagana (Journal of Management and Creative Business, 2026)
Stress on the performance of Grab driver-partners operating in Semarang City. The research is grounded in the significance of driver-partner performance as a key determinant of sustainability in the online transportation industry, given that this line of work is flexible in nature yet accompanied by considerable pressure and unstable income. A quantitative approach was applied through a survey-based method. The study population comprised all active Grab driver-partners in Semarang City, from which 100 respondents were drawn through purposive sampling based on criteria including tenure, age, and monthly order volume. Data were gathered via a five-point Likert-scale questionnaire and subsequently processed through multiple linear regression analysis using SPSS software. Findings reveal that the compensation system exerts a positive and significant influence on driver-partner performance (Beta = 0.216; Sig. = 0.016). Work flexibility was found to have the strongest positive and significant impact among the variables examined (Beta = 0.578; Sig. = 0.000). Job stress likewise demonstrated a positive and significant influence on performance (Beta = 0.134; Sig. = 0.048). Taken together, the three independent variables were shown to significantly affect driver-partner performance (F = 63.511; Sig. = 0.000), accounting for 65.4% of the variance (Adjusted R Square = 0.654). These findings suggest that work flexibility serves as the most decisive factor in enhancing driver-partner performance, alongside the continued importance of equitable compensation and sound stress management. This study is intended to provide input for PT Grab Indonesia in formulating more effective partnership policies going forward.